IMPLEMENTATION OF THE CROWD PERMIT POLICY IN AN EFFORT TO CURB COMMUNITY ACTIVITES AT THE POLICE STATION OF KECAMATAN TANETE RIAJA KABUPATEN BARRU - Kasmiah Ali; Irnawati Tahir (P3M Stia Al Gazali Barru and Meraja media, 2021)
Copyright (c) 2021 Meraja journal